MAINTAINING THE HUMOROUS EFFECT OF DARK JOKES IN INDONESIAN SUBTITLES OF RICK AND MORTY - Daniel Sbastian; Ribka Angeline Rohaedi (DIALEKTIKA: JURNAL BAHASA, SASTRA DAN BUDAYA, 2026)
Abstract Translating humor, particularly dark humor, poses considerable challenges in audiovisual translation because its comic effect depends on cultural references, pragmatic meaning, and audience tolerance for taboo subjects. While prior research has largely focused on classifying translation techniques, comparatively little attention has been paid to whether these techniques actually preserve humorous effect. This study examines how English dark jokes are translated into Indonesian subtitles in the animated series Rick and Morty, focusing on the strategies used and the extent to which they maintain the original humorous effect. Using a qualitative descriptive design, five purposively selected dark-joke instances from five episodes on the official Prime Video platform were analyzed through Chiaro's (2006) framework of humor translation techniques and Nida's (1964) concept of dynamic equivalence. The findings show that literal translation, adaptation, modulation, and omission are the main strategies employed by the translator. Adaptation and modulation prove most effective when cultural or pragmatic differences prevent literal rendering, whereas omission tends to weaken comic impact despite retaining propositional meaning. Four of the five translations achieved full or near-full dynamic equivalence. These results suggest that preserving dark humor requires prioritizing pragmatic and emotional equivalence over lexical correspondence, offering practical implications for translators working with culturally sensitive comedic content. Keywords: audiovisual translation; dark humor; dynamic equivalence; subtitle translation; Rick and Morty